Etyka „otwarta” na religię. Krytyka założeń teorii sekularyzacji opartej na koncepcji José Luis López Arangurena - Charchuła, Jarosław (Warszawskie Studia Teologiczne, 2019)
The article presents assumptions of the concept of “open” ethics to religion. It is a model of the relationship between ethics and religion developed by José Luis López Aranguren. The presented justification reveals the shortcomings of the theory of secularization. For Aranguren, the postulate of openness of ethics to religion is a logical consequence, a proper recognition of the subject of ethics and its methodology. In this way, the Spanish thinker justifies the fact that the postulate he promotes is not a theoretical construct but stems from an adequate recognition of the limits that ethics holds.